Prevalence of tinnitus in type II diabetes mellitus with or without hypertension patients in Universiti Kebangsaan Malaysia Medical Centre - Baharudin, Asyran Syamim; Ng, Chun Kiat; Isahak, Nurul Farhana; Tan, Wan Xin; Ahmad Zhaki, Fatin Nabilah; Abdul Rashid, Norsyahidah; Amir Hamzah, Siti Sofina; Hashim, Noor Dina; Abdullah, Asma; Shahar, Mohammad Arif (Japan International Cultural Exchange Foundation, 2017)
Objective: Tinnitus is perception of sound without external stimulus. Our main objective is to determine the prevalence of tinnitus in Type II diabetes mellitus patients with or without hypertension in Universiti Kebangsaan Malaysia Medical Centre. We would also evaluate the quality of life of these patients. The association between tinnitus and glycaemic control and the association with renal function were also looked into. Design: A cross sectional study was conducted from May to July 2015 among 186 respondents with type II diabetes mellitus with or without hypertension using random sampling from the Endocrine clinic, Universiti Kebangsaan Malaysia Medical Centre (UKMMC) Materials and Methods: The respondents were assessed using Tinnitus Handicap Inventory (THI) and laboratory results including HbA1c and renal function were used. Those patients with tinnitus also had pure tone audiometry test to determine the hearing levels. Results: Respondents consisted of 75 males (40.3%) and 111 females (59.7%) with mean age of 60.99 ± 11.6 years old. The racial distribution was 104 Malay (55.9%), 52 Chinese (28.0%), 27 Indian (14.5%) and 3 others (1.6%). The prevalence of patients with tinnitus was 9.1% (17 patients). There was no significant association observed between tinnitus and glycaemic control (p = 0.850) and the severity of renal function calculated from glomerular filtration rate (p = 0.253). Among 17 patients with tinnitus, 10 (58.82%) had grade 1 tinnitus severity, 5 (29.41%) had grade 2 and only 2 (11.76%) had grade 4 tinnitus severity. Conclusion: There was a small percentage of tinnitus in patient with background diabetes. There was no significant association between tinnitus and type II diabetes mellitus or severity of renal function. Tinnitus did not cause a negative impact in the majority of patients.